Dialogues between Dance at School and Dance at TikTok: Proposals in remote educacion (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
Based on the experiences of Dance as a school subject at UFPE and UFRGS Application Schools in 2020, this work shares propositions of remote dance creation activities using TikTok. The research reflect on the theoretical-methodological assumptions of these proposals in search of a dialogical praxis, using the application duets resource as a possible metaphor for the construction of knowledge in Dance at school. It is observed that this artistic-pedagogical research was an interesting way of understanding the references of dance of the youth, which allowed the investigation in Dance, by teachers and students, in a horizontal, creative and contextualized way.
Keywords: Basic education; Dance pedagogy; Social networks; COVID-19 pandemic; Dialogicity